Diagnóstico y tratamiento inicial de la oclusión intestinal del intestino delgado - Valdiviezo Espinoza, Glenda Mariuxi (Machala : Universidad Técnica de Machala, 2020)
Introduction: The intestinal obstruction constitutes an abrupt cessation of the transit of the digestive content, which can be etiologically of mechanical, nervous and vascular cause. Objective: Describe the main characteristics of the initial diagnostic and therapeutic behavior of intestinal occlusion of the small intestine. Methods and Materials: This descriptive study was carried out by reviewing scientific articles that address these nosological entities to improve the prognosis of these patients, these being published through a maximum filter of 5 years, compiled from bibliographic sources such as: PubMed, Google Academic, Current Problems in Surgery. Results: It was compared from 15 bibliographic reviews where they define intestinal occlusion as an abrupt cessation of the transit of the digestive content, which can be etiologically of mechanical, nervous and vascular cause. Patients with this nosological entity have abdominal distension, absence of gas expulsion through the anus, increased peristalsis (in mechanical causes) and severe abdominal pain, often accompanied by nausea and vomiting. Conclusion: We can affirm that the main symptoms and signs of intestinal obstruction at the level of the small intestine are presented with nausea, vomiting, abdominal pain, and constipation. The computerized axial tomography has taken greater participation in the evaluation of the patients, allowing to identify the cause of the obstruction and also to evaluate its severity.
Introducción: La obstrucción intestinal constituye un cese brusco del tránsito del contenido digestivo, lo cual puede ser etiológicamente de causa mecánica, nerviosa y vascular. Objetivo: Describir las características principales de la conducta diagnóstica y terapéutica inicial de la oclusión intestinal del intestino delgado. Metodos y Materiales: Se realizó este estudio descriptivo mediante la revisión de artículos científicos que aborden estas entidades nosológicas para mejorar el pronóstico de estos pacientes, siendo estos publicados mediante un filtro máximo de 5 años, recopiladas de fuentes bibliograficas como: PubMed, Google Academic, Current Problems in Surgery. Resultados: Se comparó de 15 revisiones bibliograficas en donde definen a la oclusión intestinal como un cese brusco del tránsito del contenido digestivo, lo cual puede ser etiológicamente de causa mecánica, nerviosa y vascular. Los pacientes con esta entidad nosológica presentan distensión abdominal, ausencia de expulsión de gases por el ano, aumento del peristaltismo (en las causas mecánicas) y dolor abdominal intenso, frecuentemente se acompaña de náuseas y vómitos. Conclusion: Podemos afirmar que los principales síntomas y signos de la obstrucción intestinal a nivel del intestino delgado se presentan con náuseas, vómitos, dolor abdominal, y constipación. La tomografía axial computadorizada, ha tomado mayor participación en la evaluación de los pacientes, permitiendo identificar la causa de la obstrucción y también evaluar su severidad.
Keywords: OBSTRUCCION INSTETINAL; DIAGNOSTICO; TRATAMIENTO INICIAL